Metal nanoparticles fabricated by green chemistry using natural extracts: biosynthesis, mechanisms, and applications. Issue 42 (8th August 2019) - El-Seedi, Hesham R.; El-Shabasy, Rehan M.; Khalifa, Shaden A. M.; Saeed, Aamer; Shah, Afzal; Shah, Raza; Iftikhar, Faiza Jan; Abdel-Daim, Mohamed M.; Omri, Abdelfatteh; Hajrahand, Nahid H.; Sabir, Jamal S. M.; Zou, Xiaobo; et al.
Abstract : Nanoparticles (NPs) are new inspiring clinical targets that have emerged from persistent efforts with unique properties and diverse applications. Abstract : Nanoparticles (NPs) are new inspiring clinical targets that have emerged from persistent efforts with unique properties and diverse applications. However, the main methods currently utilized in their production are not environmentally friendly. With the aim of promoting a green approach for the synthesis of NPs, this review describes eco-friendly methods for the preparation of biogenic NPs and the known mechanisms for their biosynthesis. Natural plant extracts contain many different secondary metabolites and biomolecules, including flavonoids, alkaloids, terpenoids, phenolic compounds and enzymes. Secondary metabolites can enable the reduction of metal ions to NPs in eco-friendly one-step synthetic processes. Moreover, the green synthesis of NPs using plant extracts often obviates the need for stabilizing and capping agents and yields biologically active shape- and size-dependent products. Herein, we review the formation of metallic NPs induced by natural extracts and list the plant extracts used in the synthesis of NPs. In addition, the use of bacterial and fungal extracts in the synthesis of NPs is highlighted, and the parameters that influence the rate of particle production, size, and morphology are discussed. Finally, the importance and uniqueness of NP-based products are illustrated, and their commercial applications in various fields are briefly featured.